Another step up the ladder or another foot in the grave? Re-evaluating the role of formal and informal training in the career development process within Barclays Bank, 1945–1980. Issue 4 (1st October 2016) - Hollow, Matthew; Vik, Pål
Abstract: This paper uses a combination of archival sources and oral testimonies to evaluate the role that training (both internal and external) played in determining the promotion prospects of those employed by Barclays Bank during the post-World War II era. In addition to this, it also looks at the extent to which less formal training and learning practices continued to play a role in the career development process within Barclays. Ultimately, what it suggests is that, whilst moves certainly were made to modernize and formalize the Bank's staff development program during this period, there continued to be a strong attachment to many of the conservative and paternalist assumptions that had been dominant in the years prior to World War II.